2008
DOI: 10.4321/s0212-71992008000600004
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del consumo de fármacos inadecuados o no indicados en el anciano que ingresa en un Servicio de Medicina Interna

Abstract: El consumo global de fármacos en los ancianos en los países industrializados se caracteriza por dos hechos básicos; de un lado el marcado incremento, en cuanto a cantidad, evidenciado a lo largo de las ultimas décadas, situándose la media en 4,2-8 fármacos/persona/día (1-3), y de otro lado el tipo de fármacos, no todos están indicados para sus patologías, estimándose que el 97% de los ancianos que viven en residencia y el 61% de los que viven en domicilio (4) consumen un fármaco inapropiado o inadecuado. Tenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
1
0
7
Order By: Relevance
“…A population survey carried out in Spain in 2013 of 2,700 people observed that drug consumption increases with age and with the prevalence of chronic diseases: people over 65 years old consume about five more drugs than adults below this age 52 . The association between advanced age and the use of polypharmacy are factors that favor the occurrence of adverse reactions 53 . In Brazil, a descriptive study with data from the National Health Survey of 2013 observed that the prevalence of the use of drugs to treat chronic diseases was approximately 80% in the treatment of hypertension, diabetes and asthma 54 .…”
Section: Discussionmentioning
confidence: 99%
“…A population survey carried out in Spain in 2013 of 2,700 people observed that drug consumption increases with age and with the prevalence of chronic diseases: people over 65 years old consume about five more drugs than adults below this age 52 . The association between advanced age and the use of polypharmacy are factors that favor the occurrence of adverse reactions 53 . In Brazil, a descriptive study with data from the National Health Survey of 2013 observed that the prevalence of the use of drugs to treat chronic diseases was approximately 80% in the treatment of hypertension, diabetes and asthma 54 .…”
Section: Discussionmentioning
confidence: 99%
“…El consumo de fármacos se ha incrementado en las últimas dos décadas en los países industrializados de forma llamativa, afectando fundamentalmente a la población anciana [3]. Dada la importancia de la prescripción y su crecimiento interanual en el gasto, se ha potenciado el abordaje de mejoras a través de estrategias de calidad sobre la prescripción farmacológica [4,5].…”
Section: Introductionunclassified
“…Como recogen Gavilán y Villafaina [8] no hay consenso en cuanto al número de fármacos a partir del cual hablar de polimedicación, pero marcar el límite en cinco medicamentos parece ser el recurso más utilizado. Blasco et al [3] concluyen que el número total de fármacos que consume una persona es el principal factor asociado a la aparición del efecto adverso de medicación (EAM).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Estos datos son comparables a los encontrados en otros estudios españoles previos, en los que también destacaba el uso inadecuado de inhibidores de la bomba de protones y benzodiacepinas (35,79).…”
Section: Ancianosunclassified